Isotopic composition of precipitation in a topographically steep, seasonally snow‐dominated watershed and implications of variations from the global meteoric water line. Issue 24 (16th August 2016) - Tappa, Daniel J.; Kohn, Matthew J.; McNamara, James P.; Benner, Shawn G.; Flores, Alejandro N.
Abstract: The local meteoric water line (LMWL), the functional relationship between locally measured values of δ 18 O and δ 2 H in precipitation, represents the isotopic composition of water entering hydrologic systems. The degree to which the LMWL departs from the global meteoric water line (GMWL), moreover, can reveal important information about meteoric sources of water (e.g. oceanic or terrestrial) and atmospheric conditions during transport. Here we characterize the isotopic composition of precipitation within an experimental watershed in the Western US that is subject to large topographic and seasonal gradients in precipitation. Interpreting the hydrometeorologic and spatial controls on precipitation, we constructed a seasonally weighted LMWL for southwestern Idaho that is expressed by the equation δ 2 H = 7.40 × δ 18 O − 2.17. A seasonally weighted LMWL that is based on weighting isotopic concentrations by climatic precipitation volumes is novel, and we argue better represents the significant seasonality of precipitation in the region. The developed LMWL is considerably influenced by the semiarid climate experienced in southwest Idaho, yielding a slope and y‐intercept lower than the GMWL (δ 2 H = 8 × δ 18 O + 10). Moderate to strong correlations exist between the isotopic composition of precipitation from individual events and surface meteorologic variables, specifically surface air temperature, relative humidity, and precipitation amount. A strong negative correlation exists between the annual average isotopic composition of precipitation and elevation at individual collection sites, with a lapse rate of −0.22‰/100 m. Copyright © 2016 John Wiley & Sons, Ltd.